2019
DOI: 10.1097/jsa.0000000000000236
|View full text |Cite
|
Sign up to set email alerts
|

Winter Adaptive Sports Participation, Injuries, and Equipment

Abstract: As the participation rate and popularity of winter adaptive sports increases, understanding injury patterns and equipment is crucial for athletes, coaches, athletic trainers, sports physicians, prosthetists/orthotists, and all the staff involved. While the inaugural Winter Paralympics in 1976 had 17 participating countries, the most recent paralympic games in Pyeongchang, South Korea had >500 athletes from 49 different countries competing in 6 disciplines: alpine skiing, nordic skiing, sledge hockey, wheelc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…The scientific literature has demonstrated that the identification of factors that generate injuries and/or trauma, their prevalence, their type, and their nature are important issues for sports science [6,[13][14][15][16][17][18]. Only proper recognition of this problem is the basis for optimal training, without compromising the health of the athlete.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific literature has demonstrated that the identification of factors that generate injuries and/or trauma, their prevalence, their type, and their nature are important issues for sports science [6,[13][14][15][16][17][18]. Only proper recognition of this problem is the basis for optimal training, without compromising the health of the athlete.…”
Section: Discussionmentioning
confidence: 99%
“…However, from study of Clarsen et al, the incidence of sport injury seemed to be comparable between Winter Paralympic athletes and Winter Olympic athletes [ 2 ]. Among winter sports, alpine skiing, Nordic skiing, and sledge hockey were extensively regarded as the 3 most popular items in disabled athletes [ 3 ]. Meanwhile, injury risk of these winter sports items within the paralytic athlete community are frequently documented.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Modifications are created both in the rules of the game as well as the equipment that is involved in any individual adaptive sport. 15,16 Criteria for participating in these activities include an individual experiencing a substantive persistent permanent disability affecting cognition function, visual acuity, motor function, or a combination of organ systems. Common participants in adaptive sports include but are not limited to those with Cerebral palsy, Down's syndrome, Hemophilia, limb deficiency, or amputation.…”
Section: What Are Adaptive Sports?mentioning
confidence: 99%